Skrining Status Gizi Siswa Siswi di SMA Al Fattah Terboyo, Kota Semarang, Jawa Tengah - Azizah, Agtika Yasyfa Nur (FKM UIN Sumatera Utara Medan, 2025)
Semarang City is determined to reduce nutrition problems, especially among school adolescents. Data from the 2018 Riskesdas showed that the percentage of adolescents aged 16-18 years in Semarang City was 2.67% classified as very short, 14.85 classified as short, 0.43% classified as very thin, 11.65% classified as thin, and 6.92% classified as obese. Overview and concerns about health and nutrition in adolescents, especially schoolchildren, are a very important issue. Based on observations at SMA Al Fattah Terboyo, students have never measured their weight and height. This can make it difficult to solve nutritional problems in adolescents because the nutritional status of school groups is rarely monitored. Health screening can be used to anticipate and prevent nutritional problems such as undernutrition and overnutrition. One method that is relatively easy and inexpensive to do is through anthropometric nutritional status assessment that can be monitored regularly. Community service activities were carried out at SMA Al-Fattah Terboyo, Semarang City, with a total of 47 participants. The form of this activity is measuring nutritional status using anthropometric methods. The health screening results showed that the nutritional status of SMA Al-Fattah Terboyo students was mostly in the normal category (38.3%). Meanwhile, based on gender, the majority of severely underweight nutritional status is female (54.5%), the majority of underweight nutritional status is male (62.5%), and the majority of normal nutritional status is female (55.6%).